Resection of the embryologically defined uterovaginal (Mullerian) compartment and pelvic control in patients with cervical cancer: a prospective analysis. - Hockel, M.; Horn, L. C.; Manthey, N.; Braumann, U. D.; Wolf, U.; Teichmann, G.; Frauenschlager, K.; Dornhofer, N.; Einenkel, J. (Lancet Oncol, 2009)
BACKGROUND: Radical hysterectomy based on empirical surgical anatomy to achieve a wide tumour resection is currently applied to treat early cervical cancer. Total mesometrial resection (TMMR) removes the embryologically defined uterovaginal (Mullerian) compartment except its distal part. Non-Mullerian paracervical and paravaginal tissues may remain in situ despite their possible close proximity to the tumour. We propose that in patients with early cervical cancer, the resection of the Mullerian compartment will lead to maximum local tumour control with low morbidity. We also propose that the relatively high rate of pelvic failure after conventional radical hysterectomy, despite adjuvant radiation, might be a consequence of the incomplete removal of the Mullerian compartment. The aim of our study was to test these hypotheses. METHODS: We did a prospective trial to assess the effectiveness of TMMR without adjuvant radiation in patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB, IIA, and selected IIB cervical cancer. We also generated MRI-based pelvic relapse landscapes from patients who had experienced pelvic failure after conventional radical hysterectomy. FINDINGS: 212 consecutive patients underwent TMMR without adjuvant radiation. 134 patients (63%) had high-risk histopathological factors. At a median follow-up of 41 months (5-110), three patients developed pelvic recurrences, two patients developed pelvic and distant recurrences, and five patients developed distant recurrences. Recurrence-free and overall 5-year survival probabilities were 94% (95% CI 91-98) and 96% (93-99), respectively. Treatment-related grade 2 morbidity was detected in 20 (9%) patients, the most common being vascular complications. Resection of the Mullerian compartment resulted in local tumour control irrespective of the metric extension of the resection margins. The pelvic topography of the peak relapse probability after conventional radical hysterectomy indicates an incomplete resection of the posterior subperitoneal and retroperitoneal extension of the Mullerian compartment. INTERPRETATION: Resection of the embryologically defined uterovaginal compartment seems to be pivotal for pelvic control in patients with cervical cancer. TMMR without adjuvant radiation has great potential to improve the effectiveness of surgical treatment of early-stage cervical cancer. FUNDING: University of Leipzig, Leipzig, Germany.
Keywords: Adult; Aged; Disease-Free Survival; Female; Humans; Hysterectomy/*methods; Lymph Node Excision/methods; Middle Aged; Mullerian Ducts; Neoplasm Recurrence, Local/*prevention & control; Prospective Studies; Uterine Cervical Neoplasms/pathology/*surgery; Uterus/embryology; Vagina/embryology